ANALISIS PENERAPAN PSAP NOMOR 2 TENTANG REALISASI ANGGARAN BERBASIS AKRUAL PADA BADAN NARKOTIKA NASIONAL KABUPATEN MEMPAWAH TAHUN 2014 - B41111125, Muhammad Faisal Daulay (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2015)
Public sector accounting in Indonesia will continue to develop with the Government Accounting Standards (SAP) currently being set by the Government Regulation No. 71/2010. This research aimed to analyze the application of the accrual basis in accordance with Government Regulation No. 71/2010 especially PSAP No. 02 on the realization of accrual-based budgeting, the effectiveness of the implementation of the budget realization, as well as the factors that hinder the accrual-based budgeting realization report in the preparation of the budget realization report at the National Narcotics Agency of Mempawah Regency 2014. This research used a descriptive method. The results of the research revealed that based on the report of the budget use, the planned budget was IDR 1,353,080,000.00, whereas the realization was IDR 1,328,566,198.00 or approximately 98.19% of the allocated budget. Meanwhile, the unused fund in the budget year of 2014 which was IDR 24,513,802,00 was returned to the National State Budget. Keywords: Government Regulation No. 71/2010, Budget Realization Report, PSAP No. 2 on the Realization of Accrual-Based Budgeting